Expression of human CD47 in pig glomeruli prevents proteinuria and prolongs graft survival following pig‐to‐baboon xenotransplantation. (21st August 2021) - Takeuchi, Kazuhiro; Ariyoshi, Yuichi; Shimizu, Akira; Okumura, Yuichiro; Cara‐Fuentes, Gabriel; Garcia, Gabriela E.; Pomposelli, Thomas; Watanabe, Hironosuke; Boyd, Lennan; Ekanayake‐Alper, Dilrukshi K.; Amarnath, Dasari; Sykes, Megan; et al.
Abstract: Background: Nephrotic syndrome is a common complication of pig‐to‐baboon kidney xenotransplantation (KXTx) that adversely affects outcomes. We have reported that upregulation of CD80 and down‐regulation of SMPDL‐3b in glomeruli have an important role in the development of proteinuria following pig‐to‐baboon KXTx. Recently we found induced expression of human CD47 (hCD47) on endothelial cells and podocytes isolated from hCD47 transgenic (Tg) swine markedly reduced phagocytosis by baboon and human macrophages. These observations led us to hypothesize that transplanting hCD47 Tg porcine kidneys could overcome the incompatibility of the porcine CD47‐baboon SIRPα interspecies ligand‐receptor interaction and prevent the development of proteinuria following KXTx. Methods: Ten baboons received pig kidneys with vascularized thymic grafts ( n  = 8) or intra‐bone bone marrow transplants ( n  = 2). Baboons were divided into three groups (A, B, and C) based on the transgenic expression of hCD47 in GalT‐KO pigs. Baboons in Group A received kidney grafts with expression of hCD47 restricted to glomerular cells ( n  = 2). Baboons in Group B received kidney grafts with high expression of hCD47 on both glomerular and tubular cells of the kidneys ( n  = 4). Baboons in Group C received kidney grafts with low/no glomerular expression of hCD47, and high expression of hCD47 on renal tubular cells ( n  = 4). Results: Consistent with this hypothesis, GalT‐KO/hCD47 kidney grafts with high expression of hCD47 on glomerular cells developed minimal proteinuria. However, high hCD47 expression in all renal cells including renal tubular cells induced an apparent destructive inflammatory response associated with upregulated thrombospondin‐1. This response could be avoided by a short course of weekly anti‐IL6R antibody administration, resulting in prolonged survival without proteinuria (mean 170.5 days from 47.8 days). Conclusion: Data showed that transgenic expression of hCD47 on glomerular cells in the GalT‐KO donor kidneys can prevent xenograft nephropathy, a significant barrier for therapeutic applications of xenotransplantation. The ability to prevent nephrotic syndrome following KXTx overcomes a critical barrier for future clinical applications of KXTx.